036 A GWAS of LGI1-antibody encephalitis. Issue 9 (12th August 2022) - Binks, Sophie; Elliott, Kate; Sempere, Vicente; Castrillo, Sergio Muñiz; Ambati, Aditya; Harper, Andrew; Honnorat, Jerome; Mignot, Emmanuel; Knight, Julian; Irani, Sarosh
Abstract : Introduction: Patients with encephalitis with antibodies to leucine-rich glioma-inactivated 1 (LGI1-Ab-E) are typically elderly males with a distinct phenotype, and ~90% carry the class II major histocompatibility (MHC) allele, DRB1*07:01. This allele is found in ~25% of healthy controls, suggesting other genetic and environmental disease factors operate in patients with LGI1-Ab-E. Yet, a previous genome-wide associa- tion study did not find variants attaining genome-wide significance outside the MHC region. Methods: LGI1-Ab-E patients were genome-wide genotyped with standard arrays. Missing variants were imputed using Minimac4 and the Haplotype Reference Consortium panel. Population-matched controls were selected from UK Biobank. Genetic association with LGI1-Ab-E was determined with PLINK, SNPTEST and GWAMA and processed using bespoke bioinformatics pipelines. The discovery cohort of 131 French patients (92 men; 70%) was population-matched with 2613 controls (957 men; 36.6%): >6 million SNPs remained after quality control (lambda 1.04). The validation cohort comprises 97 US/UK cases (66 men; 68%) and 1940 matched controls (882 men; 45%), >5 million variants and lambda of 1. Results: We replicated the MHC association (rs2858869, p=3.371e-52 in the discovery cohort; rs2858870, p=1.085e-54 in the validation cohort) and will report the extent of non-MHC associations currently under- going bioinformatic assessment and validation.